2020
DOI: 10.1098/rsos.200628
|View full text |Cite
|
Sign up to set email alerts
|

Selection for reduced fear in red junglefowl changes brain composition and affects fear memory

Abstract: Brain size reduction is a common trait in domesticated species when compared to wild conspecifics. This reduction can happen through changes in individual brain regions as a response to selection on specific behaviours. We selected red junglefowl for 10 generations for diverging levels of fear towards humans and measured brain size and composition as well as habituation learning and conditioned place preference learning in young chicks. Brain size relative to body size as well as brainstem region size relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…The same effects were observed after only a few generations of selection on Red Junglefowl for reduced fear of humans: the tamer selection line evolved a proportionally smaller brain as a whole and a proportionally smaller telencephalon, but a proportionally larger cerebellum [4]. This was associated with changes in fear memory [21]. The differences previously observed between the two selected Red Junglefowl-lines can be caused by many different factors, including genetic drift.…”
Section: Discussionsupporting
confidence: 61%
“…The same effects were observed after only a few generations of selection on Red Junglefowl for reduced fear of humans: the tamer selection line evolved a proportionally smaller brain as a whole and a proportionally smaller telencephalon, but a proportionally larger cerebellum [4]. This was associated with changes in fear memory [21]. The differences previously observed between the two selected Red Junglefowl-lines can be caused by many different factors, including genetic drift.…”
Section: Discussionsupporting
confidence: 61%
“…Overall, WL were more vigilant than RJF, and birds from the RJF LF line decreased their vigilance over testing days, while this was not the case for the RJF HF line. These results agree, to a certain extent, with previous studies on that domestication and selection for low fear of humans (a major feature of domestication) alters how birds cope and habituate to frightening stimuli [36,39,47]. Due to the small sample The failure of the tested birds to discriminate between the two tested intraspecific calls is in stark contrast to previous fundamental work on chicken vocalizations, which shows that chicken possess abilities in discriminating different types of calls [11][12][13][14][15][16]48].…”
Section: Discussionsupporting
confidence: 89%
“…We first compared the behavioral reaction of domesticated White Leghorn (a breed selected for egg production) and unselected Red Junglefowl hens. Then, we compared the behavior of Red Junglefowl hens selected across 11 generations for high or low fear of humans, a proxy to investigate early effects of domestication [36][37][38]. We hypothesize that domestication would reduce the need of animals from certain breeds/lines (here, the White Leghorn and Red Junglefowl selected for low fear of humans) to react to alarm calls (through less vigilance behavior), since domesticated animals are mainly selected to thrive in a human-controlled environments, where predators are absent.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies from our group have shown that selection for increased tameness in the ancestral red junglefowl (RJF) changes other traits in a correlated fashion and appears to drive the evolution of a domesticated phenotype, similar to what was found in the famous Farm-Fox studies [ 10 ]. For example, RJF selected for increased tameness grow larger, have a higher feed efficiency, lay larger eggs, and have a smaller brain relative to body size, while cerebellum size has increased relative to total brain mass [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%